A clinical evaluation on the effect of astringent on keratinization of oral mucosa before and after the insertion of complete denture - Rohit S Menon; M R Dhakshaini; Anil Kumar Gujjari; Usha Hegde (Wolters Kluwer Medknow Publications, 2019)
Context: Conventional complete dentures still remain a viable method of treatment for many patients in this era of fixed prosthesis like dental implants. All patients undergoing complete denture treatment need nonsurgical preprosthetic treatment for the preparation of healthy denture bearing mucosa as well-keratinized healthy mucosa is desirable for a complete denture. Aims: To evaluate and compare the keratinization before and after denture insertion at intervals of 1 week and 1 month. Settings and Design: The present study was conducted on 24 completely edentulous male subjects divided into control and study groups. Each patient in study group was asked to massage with astringent on the denture bearing mucosa over a 4-week period. Subjects and Methods: Exfoliative cytology was used to collect the surface cells from the palatal mucosa and buccal mucosa. The first smear was taken before the denture insertion. The second and third smears were taken after the stimulation treatment with astringent gel for each patient after 1 week and after 4 weeks. Each smear was stained with the Papanicolaou's technique. The number of basal cells, intermediate cells, and superficial cells were recorded to calculate the degree of keratinization. Statistical Analysis Used: Descriptive statistics, paired samples t-test, independent t-test, and repeated-measures analysis of variance. Results: The result showed statistically significant increase in the keratinization of palatal mucosa after 4 weeks of astringent therapy and no effect was noted in the keratinization of buccal mucosa. Conclusions: Astringent has shown to increase keratinization of palatal mucosa, and so it can be used to increase the quality of the denture bearing mucosa; moreover, the astringent stimulation has no effect on the keratinization of buccal mucosa.